CURRENT PROBLEMS AND FUTURE ASPECTS OF PHARMACOVIGILANCE IN INDIA - A. K. GHOSH; A. DE; N. N. BALA (International Journal of Pharma and Bio Sciences, 2010)
Pharmacovigilance is related to the protection of public health and adverse drug reaction. While major advancements of the discipline of pharmacovigilance have taken place in the West, not much has been achieved in India. However, with more clinical trials and clinical research activity being conducted in India, there is an immense need to understand and implement pharmacovigilance. Now in India, pharmacovigilance has progressed from the situation as it was in past, but for different types of problems and limitations progress is yet not very rapid. So awareness is required for improvement of pharmacovigilance as well as public health. This review is aimed to offer an analytical study of current problems and future aspects of pharmacovigilance in India. The necessity of implementation of appropriate pharmacovigilance, its requirements, problems, limitation and the process how it can be more improved have been emphasized.